Palynology of the 112.8–197.8 m interval of the core Tenaghi Philippon III, Middle Pleistocene of Macedonia - Van Der Wiel, A M; Wijmstra, T A (Review of Palaeobotany and Palynology, 1987)
In this article the palynological record of the Tenaghi Philippon III core (112.8–197.8 m) from the Philippi Plain in Greece is discussed. The arboreal pollen diagrams show an alteration of steppe phases (representing glacial periods) and oak forest phases (coinciding with interglacial periods). A proposal for a local biostratigraphy is given and a preliminary correlation is suggested with the Northwest European subdivision of the Middle Pleistocene. From the AP diagrams it appears that the flora is gradually impoverished in Arcto-Tertiary elements and obtains a more mediterranean character. In this section, however, the real mediterranean forest, rich in Quercus ilex/coccifera type is not yet present, which implies that a warm humid climate dominated with rainfall throughout the year. The presence of a great number of Tertiary pollen, two sterile intervals and clastic sediment in the lower part of the core, while from 181.6 m upwards organic sediment is found, indicates a change in sedimentation regime around a depth of 182 m. The sedimentation regime changed from fluvatile to lacustrine as a result of the aftermath of tectonic events. Chronostratigraphy of the diagrams is based on radiocarbon dates from the TF2 core, paleomagnetic polarity determinations in the TF3 core as well as interpolations between the two. In this way the core was dated at 900,000-approx. 600,000 yr B.P. A correlation with deep-sea Core V28–239 is proposed. From this correlation it appears that both in the diagrams and in the oxygen isotope curve the glacial and interglacial periods of the Middle Pleistocene are of a different wavelength and amplitude as compared to the ones of the Upper Pleistocene.
Keywords: Biostratigraphy; Chronostratigraphy; palynology; vegetation history (PG)

The place of the Tenagi Philippon in the Pleistocene stratigraphical sequence - Wijmstra, T A (Zeitschrift der Deutschen Geologischen Gesellschaft, 1972)
From an analysis of a 120 m section in Eastern Macedonia a sequence steppe and forest phases became evident. By C14 analysis it could be proved that during the stadial phases within the Weichselian an open Artemisia-Chenopodiaceae steppe existed in the area. On the other hand during the interstadials, shrub steppe phases in which pine and oak were present, existed in the area. During the interglacials forest was found. In these forests a Carpinus-Ulmus belt was succeeded by a Pinus nigra-Abies zone. In this zone the presence of Ericaceae is of importance (WIJMSTRA 1969). It became also clear from the analysis of this section that the glacial phases were equally long, but in each glacial the development of the Vegetation sequence and consequently of the climate was different. It was possible to establish the position of the Holstein interglacial either at a depth between 78 and 70 m or between 62 and 62.5 m. In this interglacial the presence of Pterocorya is worth mentioning, also Buxus and Myrtus were found in this interval. In the first phase between 87 and 105 m a series of three humid zones existed. In these zones Carpinus and Ulmus were important constituents of the Vegetation. These zones were found separated by long dry periods when the forest was dominated by Pinus nigra, Pinus heldreichii and evergreen oaks from the group Quercus ilex/coccifera. In this dry type of forest frequently naturally buming lead to open places. On these open places at first an Artemisia-Chenopodiaceae Vegetation was present.
Keywords: climatology Greece (Macedonia); Flora; Pleistocene; prairie-zone